Iron 10‐Thiacorroles: Bioinspired Iron(III) Complexes with an Intermediate Spin (S=3/2) Ground State. Issue 10 (29th January 2014) - Sakow, Dimitri; Baabe, Dirk; Böker, Birte; Burghaus, Olaf; Funk, Markus; Kleeberg, Christian; Menzel, Dirk; Pietzonka, Clemens; Bröring, Martin
Abstract A first systematic study upon the preparation and exploration of a series of iron 10‐thiacorroles with simple halogenido (F, Cl, Br, I), pseudo‐halogenido (N3, I3) and solvent‐derived axial ligands (DMSO, pyridine) is reported. The compounds were prepared from the free‐base octaethyl‐10‐thiacorrole by iron insertion and subsequent ligand‐exchange reactions. The small N4 cavity of the ring‐contracted porphyrinoid results in an intermediate spin (i.s., S=3/2) state as the ground state for the iron(III) ion. In most of the investigated cases, the i.s. state is found unperturbed and independent of temperature, as determined by a combination of X‐ray crystallography and magnetometry with 1H NMR‐, EPR‐, and Mössbauer spectroscopy. Two exceptions were found. The fluorido iron(III) complex is inhomogenous in the solid and contains a thermal i.s. (S=3/2)→high spin (h.s., S=5/2) crossover fraction. On the other side, the cationic bis(pyridine) complex resides in the expected low spin (l.s., S=1/2) state. Chemically, the iron 10‐thiacorroles differ from the iron porphyrins mainly by weaker axial ligand binding and by a cathodic shift of the redox potentials. These features make the 10‐thiacorroles interesting ligands for future research on biomimetic catalysts and model systems for unusual heme protein active sites.